2022
DOI: 10.21203/rs.3.rs-2228878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diabetes and periodontitis: Bi-directional association in population-based 15-year retrospective cohorts

Abstract: Two-way relationship between periodontitis and diabetes was advocated; however, bidirectional observation in general population is still inconclusive. Using the Taiwan Health Insurance Database (covering over 99% of the entire population),11,011 patients with severe periodontitis were recruited from 2000 to 2015.After matching by age, sex, and index date, 11,011 patients with mild periodontitis and 11,011 non-periodontitis controls were registered. The outcome of T2DM was traced. Conversely, the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Over the past decades, an increasing body of research has sought to elucidate the intricate relationship between these seemingly disparate yet interconnected fields. Diabetes, a chronic metabolic disorder characterized by hyperglycemia, not only affects systemic health but also manifests significant repercussions on oral health and its associated structures [ 1 - 7 ]. Type 2 diabetes is posing major health challenges and a public health burden in adolescents too [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, an increasing body of research has sought to elucidate the intricate relationship between these seemingly disparate yet interconnected fields. Diabetes, a chronic metabolic disorder characterized by hyperglycemia, not only affects systemic health but also manifests significant repercussions on oral health and its associated structures [ 1 - 7 ]. Type 2 diabetes is posing major health challenges and a public health burden in adolescents too [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to these intertwined health challenges, researchers across various disciplines have investigated the complex associations between diabetes and oral health [ 1 - 7 , 12 - 14 ]. Given the expanding literature landscape in this domain, a comprehensive bibliometric analysis presents an invaluable opportunity to systematically map the research trajectory, identify key thematic areas, and discern emerging trends.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis, a significant contributor to the overall global disease burden, represents a public health problem [1]. Increased by 8.44% (6.62-10.59%) in just 20 years, the age-standardized prevalence rate of periodontitis reached 13,109 (9,385) per 100,000 people in 2019 [2]. Epidemiologic studies indicating a correlation between periodontitis and at least 43 systemic diseases, including type 2 diabetes (T2D) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…T2D is associated with serious complications and mortality, resulting in low quality of life and substantial socioeconomic burden [8]. Periodontitis patients have been reported to have a higher risk of T2D, with severe periodontitis increasing the risk of T2D by 53% [9][10][11]. Another study indicates that moderate or severe periodontitis is related to a higher risk of all-cause mortality in diabetes patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested a strong bidirectional relationship between periodontitis and type 2 diabetes mellitus (T2DM). [ 3 4 5 ] Studies showed a higher prevalence of periodontal disease in patients with T1DM than in healthy individuals,[ 6 7 ] but there was less impact of periodontal treatment on glycemic control in T1DM. [ 7 ] However, Peruzzo et al [ 8 ] reported that periodontal treatment was effective for glycemic control in patients with T1DM.…”
Section: Introductionmentioning
confidence: 99%